Excipient and Dose per Unit Area Affect Sensitivity When Patch Testing With Gold Sodium Thiosulfate. Issue 5 (September 2018) - Hamann, Dathan; Bruze, Magnus; Fowler, Joseph F.; Hamann, Carsten R.; Andersen, Klaus E.; Hamann, Curt P.
Abstract : Background: Dose/area and reading paradigms for gold patch testing are controversial and not standardized worldwide. Objectives: The aims of this study were to determine the optimum patch test dose of gold sodium thiosulfate (GST) in a hydrogel (HYD) and to establish GST HYD safety/efficacy and further characterize normal morphology and time course of GST reactions. Methods: Twenty gold-allergic patients were patch tested with a dilution series of GST HYD and with GST 2% petrolatum (pet). Furthermore, this previously determined optimal dose was compared with GST 0.5% pet in 19 known-allergic and 216 consecutive subjects. Results: The optimal GST HYD dose was 0.075 mg/cm 2, not statistically different from GST 2% pet ( P = 0.4795). Gold sodium thiosulfate HYD outperformed GST 0.5% pet in both known-allergic subjects (79% vs 63%, P = 0.2482) and consecutive subjects (30% vs 9%, P < 0.0001). Late reactions were common in consecutive patients with both HYD and pet. Significantly more persistent reactions were associated with GST HYD than with GST 0.5% pet. Conclusions: Gold sodium thiosulfate HYD 0.075 mg/cm 2 is the optimal dose for diagnosis of gold contact allergy with GST. Gold sodium thiosulfate 0.5% pet yielded false-negatives in some patients, suggesting inadequate dose per centimeter squared. Late reads are normal, expected, and necessary for diagnosis of gold contact allergy in this cohort. Abstract : Supplemental digital content is available in the text.